Functional Flexibility of Exosomes and MicroRNAs of Intestinal Epithelial Cells in Affecting Inflammation - Park, Eun Jeong; Shimaoka, Motomu; Kiyono, Hiroshi (Frontiers in Molecular Biosciences, 2022)
Intestinal epithelial cells (IECs) are a mucosal immune barrier essential to coordinate host-microbe crosstalk. Sepsis is a systemic inflammatory syndrome with dysfunction in multiple organs including the intestine whose epithelial barrier is deregulated. Thus, IECs are a main contributor to intestinal permeability and inflammation in sepsis. Exosomes emerge as a mediator of intercellular and inter-organic communications. Recently, IEC-derived exosomes and their cargoes, such as microRNAs (miRNAs), in sepsis were shown to regulate expression of proinflammatory mediators in the inflamed gut tissues. It is a compelling hypothesis that these IEC exosomes exhibit their dynamic activity to deliver their functional miRNA cargoes to immune cells in local and distant organs to regulate proinflammatory responses and alleviate the tissue injury. Also, epithelial tight junction (TJ) proteins are downregulated on gut inflammations. Some of IEC miRNAs were reported to deteriorate epithelial integrity by diminishing TJ expressions in intestines during sepsis and aging. Thus, it is a worth revisiting and discussing the diverse functions of IEC exosomes and miRNAs in reshaping inflammations. This work includes both iterative and hypothetical statements based on current knowledge in this field.